2010
DOI: 10.1002/ijc.25235
|View full text |Cite
|
Sign up to set email alerts
|

Substantial regional differences in human herpesvirus 8 seroprevalence in sub‐Saharan Africa: Insights on the origin of the “Kaposi's sarcoma belt”

Abstract: Equatorial Africa has among the highest incidences of Kaposi's sarcoma (KS) in the world, thus earning the name “KS Belt.” This was the case even before the HIV epidemic. To date, there is no clear evidence that HHV‐8 seroprevalence is higher in this region but interpretation of the available literature is tempered by differences in serologic assays used across studies. We examined representatively sampled ambulatory adults in Uganda, which is in the “KS Belt,” and in Zimbabwe and South Africa which are outsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
87
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(97 citation statements)
references
References 45 publications
7
87
2
1
Order By: Relevance
“…However, unexpectedly, we found a significant higher prevalence of the virus in female children's saliva. Despite it is known that African Kaposi Sarcoma affects mainly male population, the infection in endemic areas seems to occur with the same frequency in both gender (4,6,7,11,12). Thus, the data we found are not in agreement with previous studies.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…However, unexpectedly, we found a significant higher prevalence of the virus in female children's saliva. Despite it is known that African Kaposi Sarcoma affects mainly male population, the infection in endemic areas seems to occur with the same frequency in both gender (4,6,7,11,12). Thus, the data we found are not in agreement with previous studies.…”
Section: Discussioncontrasting
confidence: 57%
“…Interestingly, in Amerindian tribes HHV-8 is hyperendemic showing the highest infection rates ever reported (about 80% in adults) (9,10). In Uganda HHV-8 seroprevalence ranges from 26.6% in children to 40.1% in adults showing an age dependent increase during childhood (7,11,12). In several studies is reported that saliva is the major reservoir of HHV-8 (5,9,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11] This may be explained by the comparatively low rates of endemic Kaposi's sarcoma in SA [16] and the lower prevalence of human herpesvirus infection in SA than, for example, in Uganda. [17] The overall incidence rates for the white population (ASR 116.2 per million) are rather low, but comparable with rates observed in the 1980s in some populations of South America (ASR 118 -136 per million) and Eastern Europe (ASR ~125 per million). [10] The higher incidence rates in the white compared with the black African population may be explained by a better rate of diagnosis and access to tertiary healthcare treatment in a POU.…”
Section: Discussionmentioning
confidence: 78%
“…The "KS belt" is a region in equatorial Africa where even before HIV, the progression of HHV-8 to endemic KS was particularly high [16]. The belt extends from the coast of Cameroon through northeast Democratic Republic of Congo and down the Rift Valley to Malawi including Uganda, Tanzania, and Zambia [17].…”
mentioning
confidence: 99%